Camp-Induced Histones h3 Dephosphorylation Is Independent of Pka and Map Kinase Activations and Correlates with Mtor Inactivation - Rojas-Pavez, J; Rodriguez-Collazo, P (Wiley-Liss Inc., 2016)
cAMP is a second messenger well documented to be involved in the phosphorylation of PKA, MAP kinase, and histone H3 (H3). Early, we reported that cAMP also induced H3 dephosphorylation in a variety of proliferating cell lines. Herein, it is shown that cAMP elicits a biphasic H3 dephosphorylation independent of PKA activation in cycling cells. H89, a potent inhibitor of PKA catalytic sub-unite, could not abolish this effect. Additionally, H89 induces a rapid and biphasic H3 serine 10 dephosphorylation, while a decline in the basal phosphorylation of CREB/ATF-1 is observed. Rp-cAMPS, an analog of cAMP and specific inhibitor of PKA, is unable to suppress cAMP-mediated H3 dephosphorylation, whereas Rp-cAMPS effectively blocks CREB/ATF-1 hyper-phosphorylation by cAMP and its inducers. Interestingly, cAMP exerts a rapid and profound H3 dephosphorylation at much lower concentration (50-fold lower, 0.125 mM) than the concentration required for maximal CREB/ATF-1 phosphorylation (5 mM). Much higher cAMP concentration is required to fully induce CREB/ATF-1 gain in phosphate (5 mM), which correlates with the inhibition of H3 dephosphorylation. Also, the dephosphorylation of H3 does not overlap at onset of MAP kinase phosphorylation pathways, p38 and ERK. Surprisingly, rapamycin (an mTOR inhibitor), cAMP, and its natural inducer isoproterenol, elicit identical dephosphorylation kinetics on both S6K1 ribosomal kinase (a downstream mTOR target) and H3. Finally, cAMP-induced H3 dephosphorylation is PP1/2-dependent. The results suggest that a pathway, requiring much lower cAMP concentration to that required for CREB/ATF-1 hyper-phosphorylation, is responsible for histone H3 dephosphorylation and may be linked to mTOR down regulation. © 2015 Wiley Periodicals, Inc.